DAMPAK AKUNTABILITAS, TRANSPARANSI PENGELOLAAN FISKAL DAN KEBIJAKAN DESA TERHADAP KESEJAHTERAAN MASYARAKAT DI KECAMATAN ULEE KARENG KOTA BANDA ACEH - Handayani, Meutia Handayani (Pusat P2M Politeknik Negeri Batam, 2023)
This investigation examines the impact of accountability, transparency in village financial management, and village policies on community well-being in Ulee Kareng District, Banda Aceh City, both partially and together. The research was conducted quantitatively. Multiple linear regression analysis was performed using SPSS 25. Primary and secondary data are used in this research. The questionnaire was used to collect data. This research included 36 village officials, consisting of 4 heads, secretary, finance and welfare from 9 villages in Ulee Kareng district. IThis investigation demonstrated that community well-being is partially influenced by three factors: accountability in village financial management, transparency in village financial management, and village policy. Community well-being in Ulee Kareng District, Banda Aceh City is also affected by accountability, transparency in financial management and village policies.